2015
DOI: 10.1111/pcmr.12424
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic factors can mediate resistance to BRAF inhibition in central nervous system melanoma metastases

Abstract: SummaryHere, we retrospectively review imaging of 68 consecutive unselected patients with BRAF V600‐mutant metastatic melanoma for organ‐specific response and progression on vemurafenib. Complete or partial responses were less often seen in the central nervous system (CNS) (36%) and bone (16%) compared to lung (89%), subcutaneous (83%), spleen (71%), liver (85%) and lymph nodes/soft tissue (83%), P < 0.001. CNS was also the most common site of progression.Based on this, we tested in vitro the efficacy of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…Tumor necrosis factor a (TNF-a) production by tumor-associated macrophages can also protect melanoma cells from BRAF therapies (Smith et al 2014) and soluble factors in cerebrospinal fluid can reduce the efficacy of BRAF inhibitors. This may partially explain the poor response of brain metastases to vemurafenib (Seifert et al 2016). Fibroblast-derived HGF has also been implicated in the resistance of EGFR mutant lung cancer to EGFR inhibitors (Wang et al 2009).…”
Section: Microenvironmental Protection From Targeted Therapiesmentioning
confidence: 99%
“…Tumor necrosis factor a (TNF-a) production by tumor-associated macrophages can also protect melanoma cells from BRAF therapies (Smith et al 2014) and soluble factors in cerebrospinal fluid can reduce the efficacy of BRAF inhibitors. This may partially explain the poor response of brain metastases to vemurafenib (Seifert et al 2016). Fibroblast-derived HGF has also been implicated in the resistance of EGFR mutant lung cancer to EGFR inhibitors (Wang et al 2009).…”
Section: Microenvironmental Protection From Targeted Therapiesmentioning
confidence: 99%
“…GRO activates CXCR2 signaling in melanoma cells, which overcomes BRAF inhibition as well as BRAF/MEK combination therapies (73). BRAF inhibition shows also efficacy in brain metastases (74), but it has been suggested that ERK-and PI3K-activating extrinsic factors contained in cerebrospinal fluid might contribute to BRAF inhibitor resistance in this setting (75). Finally, upon BRAF inhibitor treatment, specific soluble factors can sustain the proliferation of innate resistant cells that normally present as slow cycling cells in therapy naïve tumors (76,77).…”
Section: Mapk-reactivation Independent Mechanisms Of Resistance To Brmentioning
confidence: 99%
“…This pathway has also been associated with resistance to BRAF inhibitors, and preclinical in vitro and in vivo studies support that PI3K pathway inhibitors may be an effective strategy for MBMs as single agents or in combination with BRAF inhibitors. 15,17,18 A phase II trial of the pan-PI3K inhibitor buperlisib (BKM120) in patients with MBMs is currently ongoing [Table 2]. Additional studies support that increased signaling by the JAK-STAT signaling pathway may be associated with MBM, and a phase II trial of the STAT3 inhibitor WP-1066 in MBM patients is underway.…”
Section: Targeted Therapymentioning
confidence: 99%